Hybrid Implant-supported Prosthesis in the Lower Arch: A Case Report - Sangram Panda1, Sitanshu Sekhar Das2, Abhijita Mahapatra2, Abhilash Mohapatra2, Pradyumna Sahoo1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The protocols for the implant dentistry has improved at a very extreme pace. To conduct implant dentistry ina manner that is beneficial for the society requires an impeccable diagnosis, a treatment plan that takes intoconsideration surgical and prosthetic parts too. For any implant driven prosthesis to be successful requiresthat clinicians adhere to the basic principles ignoring which can lead to a prosthodontic nightmare. Followingis a case report describing the methodology followed for hybrid lower implant-supported prosthesis